1983
DOI: 10.1002/cjce.5450610310
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of fine particles in a spouted bed consisting of fine and coarse particles

Abstract: The elutriation of fines from a spouted bed of fine and coarse particles has been studied. Equations for correlating elutriation rate coefficients are proposed. Three different regions associated with particle behavior have been identified in a way to permit calculation of elutriation rate at any column height. Measurements of cross‐sectionally averaged holdup of particles and local particle velocity have been used to interpret the decrease in elutriation rate along the freeboard. The known concept of a Transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…E-mail address: ishikura@fukuoka-u.ac.jp important to investigate the behaviour of cohesive powders within the PPSB. Although Ishikura et al (1983Ishikura et al ( , 1984 examined the behaviour of fine particles in a spouted bed consisting of fine and coarse particles, they only presented the results for the case using fine particles more than 100mm in size. In addition, Xu et al (1998b) reported only on the hold-up of fines such as Geldart Group C particles in a PPSB.…”
mentioning
confidence: 99%
“…E-mail address: ishikura@fukuoka-u.ac.jp important to investigate the behaviour of cohesive powders within the PPSB. Although Ishikura et al (1983Ishikura et al ( , 1984 examined the behaviour of fine particles in a spouted bed consisting of fine and coarse particles, they only presented the results for the case using fine particles more than 100mm in size. In addition, Xu et al (1998b) reported only on the hold-up of fines such as Geldart Group C particles in a PPSB.…”
mentioning
confidence: 99%
“…It is noted that the coarse particles were observed to be covered with the fine powders when stopping both the gas flow and the fine powder feeding simultaneously at the steady state. X=WPfWPC+WPf The elutriation rate constant of fine powders ( K ) for a spouted bed consisting of fine and coarse particles was provided by Equation based on the masses of fine and coarse particles in the bed: V=KAX(1X) In this study, as X is much less than 0.1, Equation can be approximated by the following equation: V=KAX where A is the cross sectional area of the column. The elutriation rate of fine powders ( V ) is equal to the feed rate of fine powders ( F ) at steady state.…”
Section: Methodsmentioning
confidence: 99%
“…The elutriation rate constant of fine powders (K) for a spouted bed consisting of fine and coarse particles [16] was provided by Equation (2) based on the masses of fine and coarse particles in the bed:…”
Section: Methodsmentioning
confidence: 99%
“…Most of these applications involve mixtures of solids of different particle sizes, shapes, and densities, making them subject to the particle segregation phenomenon. This segregation occurs mainly due to the difference in particle terminal velocities [12,13].…”
Section: Introductionmentioning
confidence: 99%